Islamisation of Knowledge: Islamic Sociology and Anthropology in Theory and Practice - Peow, See Hoon (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Islamisation of Knowledge: Islamic Sociology and Anthropology in Theory and Practice